In vivo immunological response of exposure to PEGylated graphene oxide via intraperitoneal injection. Issue 31 (5th May 2020) - Ding, Zhaowen; Luo, Nana; Yue, Hua; Gao, Yongjun; Ma, Guanghui; Wei, Wei
Abstract : 2D PEGylated graphene oxide showed stealth-but-immune-activating capacity on macrophages, along with specific intraperitoneal immunological response in vivo . Abstract : Polyethylene glycol functionalization is believed to have the capacity of endowing nanomaterials with stealth characteristics, which can diminish the arrest by macrophages and adverse immunological response. However, our previous study provided evidences that polyethylene glycol-functionalized graphene oxide (GOP) stimulated a strong immunological response to macrophages despite non-internalization in vitro, raising safety concerns and potential immunostimulation use of GOP. In light of this finding, we herein systematically study the in vivo immunological response upon the exposure to GOP via intraperitoneal injection. Taking cytokines production, cell types in the peritoneal fluid, biochemical index, hematology and histopathology as in vivo indicators, we demonstrate that GOP still remains the stealth-but-activating capacity on macrophages in a time and dose-dependent manner. Specifically, the immune response can be significantly elevated after a single high-dose injection, indicating that GOP can be a new candidate adjuvant for immunotherapy. For multiple low dose injections, the immune response is gentle, temporary, and tolerable, which manifests the biocompatibility of GOP in general drug delivery. The above results can thus provide guidance for safe and rational use of GOP for various biomedical applications.